Development and application research of smart distribution district based on IDTT-B new-type transformer terminal unit. (2019) - Xu, Aidong; Cheng, Lefeng; Guo, Xiaobin; Jian, Ganyang; Yu, Tao; Wei, Wenxiao; Yu, Li
Amid the problems of low automation degree and failed remote monitoring of operation situation in distribution district, an ITDD-B-type of transformer terminal unit (TTU)-based smart distribution district (SDD) is designed, which provide scientific and advanced technical methods for operation management units in aspect of achieving fine management in distribution districts. The construction of SDD is stated, i.e., the upgrading and reconstruction work of original distribution district, the construction of new-type SDD based on ITDD-B TTU and the building of communication network and main station. It is focus on design of IDTT-B-type TTU and which can finish transformer monitoring, power quality monitoring, temperature measurement and low voltage switch communication, etc. and has high integration, and supports remote control, communication and software upgrading, and also has low investment and high cost performance. The technical features and total performance and application situation of IDTT-B-based SDD are introduced. Finally, an applied example of SDD based on IDTT-B is given and the power quality detection and analysis are made. The construction of new-type distribution district has certain significance for unified building of strong and smart grid, also provides certain guidance and reference for operation and management units.